Human Resource Management Implementation and Its Impact on Employee Performance - Apriliana Irawati; Sutianingsih, Sutianingsih (International Journal of Business and Quality Research, 2025)
This study aims to analyze the effect of the implementation of human resource management (HRDM) on employee performance at the Grobogan Regency DPRD Secretariat. The independent variables used are recruitment, training, and job evaluation, while the dependent variable is employee performance. The research approach used is quantitative with a causal associative design. The population of this study includes all employees of the Grobogan Regency DPRD Secretariat totaling 142 people, consisting of 37 ASN and 105 Non-ASN employees, all of which are used as a sample (census). Data were collected through questionnaires and analyzed using multiple linear regression analysis. The results of the study show that partially, recruitment, training, and job evaluation each have a positive and significant influence on employee performance. The model's predictive capabilities are very strong, shown by the Adjusted R Square value of 0.703, which means that 70.3% of employee performance variations can be explained by recruitment, training, and job evaluation.